Islamic Guidance for Drug Addiction - Agus Supriyanto (Indonesian Institute for Counseling, Education and Therapy (IICET), 2016)
Islamic Guidance is social rehabilitation program for Drug Addiction (resident). The goal of this research to know the Islamic guidance for resident at the Center for Rehabilitation of the National Narcotics Agency Lido Bogor. The methodology in this research is qualitative descriptive, with a sample two religious counselor. Can be concluded that Islamic guidance is implemented with the classical format, group format, and individual formats. The goal of the Islamic Guidance to develop religious mentally.